KURIKULUM UNTUK PEMBELAJARAN BAHASA ARAB DI SMA: TELAAH KONSEPTUAL DAN IMPLEMENTASI - Farhan, Ali; Yayan Nurbayan; Mad Ali ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
This study explores the concept and implementation of the Merdeka Curriculum, particularly in Arabic language learning at the high school level. Introduced in 2019, the Merdeka Curriculum emphasizes humanistic and innovative learning through differentiated approaches, project-based learning, and holistic assessments. This research employs a literature study method with a qualitative approach, analyzing 34 references, including books, academic journals, and supporting documents. Findings reveal that the Merdeka Curriculum provides teachers with flexibility in selecting methods and teaching materials while encouraging students to learn actively and independently. The curriculum encompasses intracurricular, co-curricular, and extracurricular learning aimed at developing character and 21st-century skills such as critical thinking, creativity, and digital literacy. However, its implementation faces challenges, including limited teacher understanding, resource constraints, and administrative hurdles. In the context of Arabic language learning, the main challenges include a lack of innovative teaching materials and teacher training. This study recommends intensive teacher training, increased access to technology, and the development of learning resources as strategic steps to support the successful implementation of the Merdeka Curriculum. By addressing these obstacles, the curriculum holds significant potential to improve educational quality and prepare students to face challenges and opportunities in the global era.